Optimal routes of administration, vehicles and timing of progesterone treatment for inhibition of delivery during pregnancy. (September 2017) - Fang, Dajun; Moreno, Mario; Garfield, Robert E.; Kuon, Ruben; Xia, Huimin
Abstract: Objectives: Progestins, notably progesterone (P4) and 17 alpha hydroxyprogesterone caproate, are presently used to treat pregnant women at risk of preterm birth. The aim of this study was to assess the optimal treatment options for progesterone (P4) to delay delivery using a sensitive bioassay for progesterone. Study design: Pregnant rats, known to be highly sensitive to progestins, were treated with P4, including Prochieve ® (also known as Crinone ® ), in various vehicles from day 13 of gestation and in late gestation, days 19 to 22, and delivery times noted. Various routes of administration of P4 and various treatment periods were studied. Results: Use of micronized P4 by rectal, subcutaneous injection (sc) and topical (transdermal) administration in various oils all significantly (P < 0.05–<0.001) delay delivery, but vaginal Prochieve ® did not. Administration of P4 in late gestation also prevented (P < 0.001) delivery even when given 8 h before delivery. Conclusions: Prochieve ® possesses little biological activity to suppress delivery in a sensitive bioassay system and suggests that this preparation may be of little value in prevention and inhibition of preterm birth. Further, this study shows: 1) Inhibition of delivery is increased with P4 treatments when given subcutaneously or topically. 2) P4 in fish oil provides the best vehicle for topical treatment and may be an effective treatment of preterm birth. 3) P4 in fish oil also delays delivery even when treatment begins just prior to normal delivery. 4) To prevent preterm birth in pregnant women, randomized controlled studies are needed with a potent progestin using better formulations and routes of administration.